2016
DOI: 10.1111/anu.12429
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary cellulase addition on growth performance, nutrient digestibility and digestive enzyme activities of juvenile crucian carp Carassius auratus

Abstract: This study was conducted to determine the effects of dietary cellulase addition on improving the nutritive value of Chlorella for juvenile crucian carp Carassius auratus (initial body weight: 2.99 ± 0.02 g, mean ± SEM). Five isonitrogenous and isoenergetic experimental diets were formulated to contain 0.0 (control), 0.5, 1.0, 1.5 and 2.0 g kg−1 cellulase, respectively. Each experimental diet was randomly assigned to triplicate groups with 25 juvenile fish per fibreglass tank for 8 weeks. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
(87 reference statements)
3
10
0
1
Order By: Relevance
“…Positive effects on the apparent digestibility of lipids were also observed when supplementing β‐glucanase to a diet containing 250 g/kg sunflower meal, or xylanase to a diet containing 260 g/kg rapeseed meal. Shi, Luo, Chen, Huang, et al () informed that dietary cellulase supplementation at the level can improve growth performance, digestive activities and nutrient digestibility in crucian carp ( Carassius auratus ). The authors revealed that cellulase is postulated to have liberated carbohydrate and protein from the endosperm cells, which increased the availability of nutrients embedded in the cell wall matrix.…”
Section: Exogenous Enzymes Currently Used In Fishsupporting
confidence: 75%
“…Positive effects on the apparent digestibility of lipids were also observed when supplementing β‐glucanase to a diet containing 250 g/kg sunflower meal, or xylanase to a diet containing 260 g/kg rapeseed meal. Shi, Luo, Chen, Huang, et al () informed that dietary cellulase supplementation at the level can improve growth performance, digestive activities and nutrient digestibility in crucian carp ( Carassius auratus ). The authors revealed that cellulase is postulated to have liberated carbohydrate and protein from the endosperm cells, which increased the availability of nutrients embedded in the cell wall matrix.…”
Section: Exogenous Enzymes Currently Used In Fishsupporting
confidence: 75%
“…The inclusion level of cellulase in diets was based on the instruction of the producer and our recent study (Shi et al . )…”
Section: Methodsmentioning
confidence: 99%
“…In addition, when 50% of FM in diets was replaced by Chlorella meal, dietary cellulase supplementation showed positive effects on growth and feed utilization in crucian carp (Shi et al . ). Thus, on the basis of our previous study, the objective of this study was to evaluate the effects of higher cellulase levels in diets with higher fish meal substitution by Chlorella meal on growth performance, digestive enzyme activities, histology and mRNA levels of myogenic factors in crucian carp.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Crucian carp is a typical omnivorous fish, which makes a more efficient use of high levels of dietary vegetable protein (Shi, Luo, Chen, Huang, et al, 2016;Silva et al, 2010). Our recent study successfully determined the optimal dietary replacement levels of FM by Chlorella in crucian carp (Shi, Luo, Huang, Zhu & Liu, 2015).…”
Section: Introductionmentioning
confidence: 99%